Monograph on indigenous chicken ecotypes in Cambodia - Esatu, Wondmeneh; Phem, M.; Hoa Hoang; Ty, C.; Tum, S.; Unger, Fred; Dessie, Tadelle (International Livestock Research Institute, 2025)
This monograph describes the Cambodian indigenous chickens phenotypic and genetic characteristics, genetic attributes related to egg and meat production, adaptability of promising chicken ecotypes and their socioeconomic contribution. Cambodia is home to a large genetic diversity of indigenous chickens that are well adapted to its various geographical locations. Indigenous chicken genetic improvement programs in the country have yielded promising results but need to emphasize the maintenance and sustainable use of this genetic diversity. This monograph is an output of the Asian Chicken Genetic Gains (AsCGG) project. It describes the Cambodian indigenous chickens’ phenotypic and genetic characteristics, genetic attributes related to egg and meat production, adaptability of promising chicken ecotypes and their socio-economic contributions. This monograph can be used by researchers, breeders, PhD and master students, NGOs and other practitioners involved in supporting chicken genetic improvement for farmers in the chicken value chain and other actors. This monograph is expected to contribute to capacity building along the value chain, leading to improved chicken genetics. This will enable farmers to transition from backyard or semi-intensive farming to more intensive, market-oriented production, enhancing production, food security and livelihoods while benefiting the wider community and countries involved.